KIT ligand protects against both light-induced and genetic photoreceptor degeneration - Li, Huirong; Lian, Lili; Liu, Bo; Chen, Yu; Yang, Jinglei; Jian, Shuhui; Zhou, Jiajia; Xu, Ying; Ma, Xiaoyin; Qu, Jia; Hou, Ling (eLife, 2020)
Photoreceptor degeneration is a major cause of blindness and a considerable health burden during aging but effective therapeutic or preventive strategies have not so far become readily available. Here, we show in mouse models that signaling through the tyrosine kinase receptor KIT protects photoreceptor cells against both light-induced and inherited retinal degeneration. Upon light damage, photoreceptor cells upregulate Kit ligand (KITL) and activate KIT signaling, which in turn induces nuclear accumulation of the transcription factor NRF2 and stimulates the expression of the antioxidant gene Hmox1. Conversely, a viable Kit mutation promotes light-induced photoreceptor damage, which is reversed by experimental expression of Hmox1. Furthermore, overexpression of KITL from a viral AAV8 vector prevents photoreceptor cell death and partially restores retinal function after light damage or in genetic models of human retinitis pigmentosa. Hence, application of KITL may provide a novel therapeutic avenue for prevention or treatment of retinal degenerative diseases.
Keywords: endogenous neuroprotection; tyrosine kinase receptor; stem cell factor; retinitis pigmentosa; antioxidative